Team spirits : the Native American mascots controversy - King, C. Richard, 1968-; Springwood, Charles Fruehling (University of Nebraska Press, 2001)
Studies the controversy over the use of Native American mascots by professional sports, colleges, and high schools, describing the origins and messages conveyed by such mascots as the Atlanta Braves and Florida State Seminoles.